Social Project as a Technology for Developing Leadership Qualities in Modern Students - L. R. Fazleeva (Высшее образование в России)
The article shows the potential of a social project in the formation of leadership qualities in students. The essence of a social project is revealed, the stages of its implementation are shown. The author focuses on the concept of leadership, considers the key qualities of a leader. One of the demanded qualities of a leader in modern life is his active life position, which is expressed in the conscious realization of his social roles. Social project facilitates the development of such activity. We used social project as a technology for the development of leadership qualities in students. To that end, we have conducted a survey among the students of the faculty of service, tourism, and technology of public catering (N=69) with the aim to reveal the leadership skills. The results of testing showed insufficient development of these skills. We have assumed that the participation of students in the development and realization of the social project would foster more intensive development of leadership qualities. The realization of the social project “Supporting of persons with impaired mobility in city infrastructure” under the guidance of teachers and experts has justified the efficiency of the implemented technology. Upon the project completion the students demonstrated better results in four positions.